APPLICATION OF SATELLITE MICROWAVE REMOTE SENSING DATA TO SIMULATE MIGRATION PATTERN OF ALBACORE TUNA - Mukti Zainuddin; Katsuya Saitoh; Sei-Ichi Saitoh (BRIN, 2011)
To simulate migration pattern of albacore tuna in the western North Pacific Ocean during the winter period, a kinesis model driven by high accuracy of sea surface temperature (SST) maps was used. The SST data were derived from the Tropical Rainfall Measuring Mission/TRMM Microwave Imager (TRMM/TMI). Simulations showed that albacore tuna aggregated in areas of thermal preference indicated by contour line of 20Â°C SST. Results are compared with empirical observation maps of albacore tuna fishing locations determined from longline fishing operation during the same time periods. Albacore tuna distributions along thermal fronts generating from Simulations were fairly consistent with fishing data especially during November-January, although seasonal variations in surface temperature ranges occupied suggest that additional oceanographic factors are involved particularly during February-March. Simulations and empirical data had similar temperature distributions at approximately 18-21Â°C and one-sample Kolmogorov-Smirnov test reinforced the result performance. These results suggest that kinesis model driven by satellite microwave remote sensing is one of effective mechanisms for describing migration pattern of tuna in the open ocean environment.